REGULATION of the EXTRACELLULAR MATRIX INTERACTOME by Trypanosoma cruzi - Cardenas, Tatiana C. (2010)
It has been shown that the invasive trypomastigote forms of Trypanosoma cruzi use and modulate components of the extracellular matrix (ECM) during the initial process of infection. Infective trypomastigotes up-regulate the expression of laminin γ-1 (LAMC1) and thrombospondin (THBS1) to facilitate the recruitment of trypomastigotes to enhance cellular infection. Silencing the expression of LAMC1 and THBS1 by stable RNAi dramatically reduces trypanosome infection. T. cruzi gp83, a ligand that mediates the attachment of trypanosomes to cells to initiate infection, up-regulates LAMC1 expression to enhance cellular infection. Infective trypomastigotes interact with LAMC1 through galectin-3 (LGALS3), a human lectin, to enhance cellular infection. Silencing the expression of LGALS3 also reduces cellular infection. Some trypanosome surface molecules also interact with the ECM to facilitate infection. Despite the role of the ECM in T. cruzi infection, almost nothing is known about the ECM interactome networks operating in the process of T. cruzi infection. In this mini review, we critically analyze and discuss the regulation of the ECM by T. cruzi and its gp83 ligand, and present the first elucidation of the human ECM interactome network, regulated by T. cruzi and its gp83 ligand, to facilitate cellular infection. The elucidation of the human ECM interactome regulated by T. cruzi is critically important to the understanding of the molecular pathogenesis of T. cruzi infection and developing novel approaches of intervention in Chagas’ disease.